2018
DOI: 10.1111/joca.12230
|View full text |Cite
|
Sign up to set email alerts
|

Policy Uncertainty and Saving Attitude: Evidence from a Survey on Consumers

Abstract: Uncertainty over the social security and tax system is often pointed out as a source of stagnant household consumption at the aggregate level. This study presents empirical evidence on this issue by using original survey data of Japanese individuals. The results indicate that individuals are highly uncertain over the future course of social security and tax policies. The policy uncertainty is associated with an orientation toward saving, and the relationship is stronger for low‐income individuals. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…While Menegatti [14] and Christelis et al [3] did not provide evidence on the impact of uncertainty on consumption behavior, Masayuki et al [13] managed to reveal the impact of uncertainty on consumption and saving behavior. This study concluded that individuals are highly uncertain about social security policies, and such uncertainty may affect their saving and consumption behavior.…”
Section: Empirical Reviewsmentioning
confidence: 99%
“…While Menegatti [14] and Christelis et al [3] did not provide evidence on the impact of uncertainty on consumption behavior, Masayuki et al [13] managed to reveal the impact of uncertainty on consumption and saving behavior. This study concluded that individuals are highly uncertain about social security policies, and such uncertainty may affect their saving and consumption behavior.…”
Section: Empirical Reviewsmentioning
confidence: 99%
“…Second, it shakes residents’ confidence and results in the increase of precautionary savings. With fixed income, consumers will make more savings and spend less in the case of greater uncertainties ( Morikawa, 2019 ). On the contrary, the weaker feelings of uncertainties will motivate consumers to spend more and save less.…”
Section: Hypothesis and Propositionmentioning
confidence: 99%
“…According to the 'precautionary saving' theory, increased uncertainty positively affects savings because households are prudent and want to seek protection from uncertainty, which causes a significant adverse impact on current consumption and positive impact on savings. Previous research have tested this theory using different uncertainty measures (Aaberge et al, 2017;Giavazzi & McMahon, 2012;Morikawa, 2019;Coibion et al, 2021). A key challenge unaddressed in the literature to quantifying the policy uncertainty effect on household savings is the role of business cycle, as both uncertainty and savings tend to increase during economic downturns (Adema & Pozzi, 2015;Duca & Saving, 2018;Ludvigson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%